Caloric Effects in Bulk Lead‐Free Ferroelectric Ceramics for Solid‐State Refrigeration. Issue 2 (28th October 2015) - Patel, Satyanarayan; Chauhan, Aditya; Vaish, Rahul
Abstract: The caloric behavior of bulk (Ba0.865 Ca0.135 Zr0.1078 Ti0.8722 Fe0.01 Nb0.01 )O3 (BCZTO‐FeNb) with respect to multiple physical inputs is investigated. Predictions were made by using modified Maxwell's relations in conjunction with independent experimental data. BCZTO‐FeNb possesses significant potential for multiple caloric effects. A peak electrocaloric effect of 0.5 K (307 K) was predicted for electric fields of 0–3 kV mm −1, significantly higher than for other BCZTO‐based compositions. A maximum elastocaloric cooling of 1.17 K (298 K) was achieved for an applied stress of 0–200 MPa (3 kV mm −1 ). Finally, a new component of the electric‐field‐driven caloric effect is reported as the inverse piezocaloric effect, with a maximum temperature change of 0.4 K (298 K). Abstract : What′s cooler, than being cool? The caloric behavior of bulk (Ba0.865 Ca0.135 Zr0.1078 Ti0.8722 Fe0.01 Nb0.01 )O3 (BCZTO‐FeNb) with respect to multiple physical inputs is investigated. Predictions were made by using modified Maxwell's relations in conjunction with independent experimental data, highlighting the efficacy of bulk ferroelectric materials as suitable candidates for solid‐state refrigeration.